2018
DOI: 10.1152/ajpheart.00390.2018
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke cognitive impairment and hippocampal neurovascular remodeling: the impact of diabetes and sex

Abstract: Diabetes increases the risk and severity of cognitive impairment, especially after ischemic stroke. Pathological remodeling of the cerebrovasculature has been postulated to contribute to poor neuronal repair and worsened cognitive deficits in diabetes. However, little is known about the effect of diabetes on the vascularization of hippocampus, a domain critical to memory and learning. Therefore we had two aims for this study: 1) to determine the impact of diabetes on hippocampal neurovascular remodeling and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 54 publications
(72 reference statements)
1
24
0
Order By: Relevance
“…However, this early antiinflammatory state is absent when similar experiments are conducted in diabetic animals and this is associated with impaired white matter repair and long-term functional deficits [11]. We also showed that diabetes, as a chronic inflammatory disease, increases the number of activated ameboid microglia and worsens cognitive outcomes of stroke [12,13]. These studies suggest that the inflammatory status of microglia can be modulated by the microenvironment [14].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, this early antiinflammatory state is absent when similar experiments are conducted in diabetic animals and this is associated with impaired white matter repair and long-term functional deficits [11]. We also showed that diabetes, as a chronic inflammatory disease, increases the number of activated ameboid microglia and worsens cognitive outcomes of stroke [12,13]. These studies suggest that the inflammatory status of microglia can be modulated by the microenvironment [14].…”
Section: Introductionmentioning
confidence: 57%
“…The high degree of macrophage infiltration in the diabetic animals brings into question the blood brain (BBB) integrity. Utilizing the same HFD/STZ model reported here, our lab has previously shown that diabetic animals have a compromised BBB that persists 14 days poststroke [13]. This brought into question whether the CSF1R silencing would improve or exacerbate the compromised BBB.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Besides, obese Zucker rats whose middle cerebral arteries underwent structural remodeling had greater cerebral injury after cerebral ischemia (Osmond, Mintz, Dalton, & Stepp, ). In addition, pathological remodeling of cerebrovasculature has been proved to contribute to poor neuronal repair and worsened cognitive deficits in rats with diabetic stroke (Ward et al, ). In clinical researches, pathological vascular remodeling has been used as an approach and an indicator to evaluate the etiology (Sun & Yuan, ), risk stratification (Wu et al, ) and therapeutic efficacy (Abraham et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic encephalopathy (DE), one of the main complications of DM, is characterized by brain infarcts [3], brain atrophy in cortex and hippocampal volume [4], cerebrovascular disfunction and morphological change [5], and impairment of synaptic plasticity [6]. Notably, an increasing amount of studies have revealed the link between diabetes and neurodegenerative disorders, such as Alzheimer's disease (AD), with changes in cognitive impairment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%